1982
DOI: 10.1111/j.1365-2141.1982.tb03928.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of acute phase, antibody‐induced haemolytic anaemia in an infant

Abstract: We describe a case of 'warm' antibody-induced haemolytic anaemia (WAIHA) in which marked depression of red cell Rh antigen expression resulted in the patient presenting with severe anaemia but a negative direct antiglobulin test (DAT). The serum contained potent IgG Rh antibodies. Unlike two previously reported cases (Koscielak, 1980; Veer et al. 1981) in which the diagnosis of WAIHA was established before the DAT became negative, this patient presented with negative serological findings during his first episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Suppression of blood group antigens has most often been documented in the setting of AIHA. [1][2][3][4][5][6][7][8][9][10][11][12][13] The precise frequency of antigen suppression in AIHA is uncertain, but approximately 10% of patients with AIHA have a negative DAT. Although the percentage of patients with DATnegative AIHA who have antigen suppression is unknown, the frequency of antigen suppression in AIHA may be significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suppression of blood group antigens has most often been documented in the setting of AIHA. [1][2][3][4][5][6][7][8][9][10][11][12][13] The precise frequency of antigen suppression in AIHA is uncertain, but approximately 10% of patients with AIHA have a negative DAT. Although the percentage of patients with DATnegative AIHA who have antigen suppression is unknown, the frequency of antigen suppression in AIHA may be significant.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From a patient with an alloantibody against a clinically significant antigen, such as Rh, Kell, Kidd, or Duffy. However, antigens in each of these blood group systems have also been shown to be capable of undergoing a process of antigen suppression in the setting of autoantibodies, [1][2][3][4][5][6][7][8][9][10][11][12][13] and antigen suppression on transfused RBCs has been confirmed in the case of several alloantibodies. 2,3 In the rare cases that crossmatchincompatible transfusions are given, either as a "least incompatible" unit or due to a clerical error, a progressive decrease in DAT is interpreted as antibody-mediated destruction of the transfused RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Ag loss has been reported involving Abs against several different blood group Ags (60)(61)(62)(63)(64)(65), there is little understanding of this phenomenon or its contribution to IgG-mediated suppression. Studies in animal models have shown that it requires the binding of multiple Abs to the RBC, and individual monoclonal Abs did not induce Ag loss (59).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This phenomenon has been reported involving antibodies against several different blood group antigens, including single-pass transmembrane proteins (Kell and Kidd) and multipass transmembrane proteins (Duffy and Rh). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Western blot analysis of human RBCs that have undergone antigen loss suggest that for at least one case of antigen loss in the Kell system, the entire protein that carries the blood group antigen is removed from the RBC, as opposed to just a destruction of the part of the molecule that constitutes the antigen. 4 Although antigen loss has been described in multiple case reports, there is little mechanistic understanding of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%